Obrazy postaci mitologicznych w oryginałach i przekładach wybranych wierszy Siergieja Gorodieckiego - Potyrańska, Agnieszka (Acta Polono-Ruthenica, 2019)
This article brings the idea on the subject of a mythopoetic approach to the characters from Slavic mythology in translations of poems by Sergey Gorodetsky into Polish. This article focuses on the following works: Полюбовники (1906) – Miłośnicy (1971) and Предки (without a date) – Przodkowie (1971). The intent is to analyse the translations and to track to what extent the trans-lator reflected the specificity of the characters from lower mythology (Russian леший, черт) pre-sented in the original, and how much their image has changed in the translation. The analysis will also focus on the “inner form of the word” (Potiebnia) to show how specific translational actions influence the perception of the lyrical situation shown in the poems. Finally, the extent to which equilinearity and equirythmicality have been preserved in the above-mentioned examples will be examined (Kwiatkowski).